Development of financial risk assessment model for overseas project investments - He, Zhi. (2008)
This research investigates the new features of overseas investments and the associated risks. Risk factors for overseas investment are assessed globally, i.e. from general economic situations, political and legal uncertainties, social and environmental conditions. Eight countries in the market have been surveyed. This research presents a new method for risk assessment of overseas investment.